Grave disturbances : the archaeology of post-depositional interactions with the dead - Aspöck, Edeltraud; Klevnäs, A. M. (Alison Margaret); Müller-Scheessel, Nils, 1970- (Studies in funerary archaeology ;, 2020)
Archaeologists excavating burials often find that they are not the first to disturb the remains of the dead. Graves from many periods frequently show signs that others have been digging and have moved or taken away parts of the original funerary assemblage. Displaced bones and artefacts, traces of pits, and damage to tombs or coffins can all provide clues about post-burial activities. The last two decades have seen a rapid rise in interest in the study of post-depositional practices in graves, which has now developed into a new subfield within mortuary archaeology. This follows a long tradition of neglect, with disturbed graves previously regarded as interesting only to the degree they revealed evidence of the original funerary deposit.This book explores past human interactions with mortuary deposits, delving into the different ways graves and human remains were approached by people in the past and the reasons that led to such encounters. The primary focus of the volume is on cases of unexpected interference with individual graves soon after burial: re-encounters with human remains not anticipated by those who performed the funerary rites and constructed the tombs. However, a first step is always to distinguish these from natural and accidental processes, and methodological approaches are a major theme of discussion.